Preparation method and application of a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material

By introducing a mixed solution of urea, manganese chloride tetrahydrate and ethanol into the lithium-sulfur battery cathode material, and combining it with the pyrolysis treatment of sodium chloride and anhydrous potassium citrate, a loaded Mn3O4 type porous composite rich in carbon defects was prepared The material solves the problem of insufficient conductivity and catalytic activity of the lithium-sulfur battery cathode material, and significantly improves the performance and stability of the battery.

CN118825184BActive Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411264338.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The conductivity and dispersion of the existing lithium-sulfur battery cathode materials are insufficient, resulting in limited catalytic activity and affecting battery performance.

Method used

After mixing the hybrid, manganese chloride chloride and ethanol, adding sodium chloride and potassium -free citric acid potassium citric aquarium -ear hot treatment after the mixing reaction is used to prepare carbon -rich MN3O4 multi -porous lithium sulfur battery composite materials Essence

Benefits of technology

It significantly improves the conductivity and intrinsic catalytic activity of Mn3O4, accelerates the conversion reaction of polysulfides in lithium-sulfur batteries, and improves the electrochemical performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825184B_ABST
    Figure CN118825184B_ABST
Patent Text Reader

Abstract

The present invention provides a carbon-defect-rich Mn-loaded 3 O 4 The invention discloses a method for preparing a porous lithium-sulfur battery composite material and its application, belonging to the technical field of preparing positive electrode materials for lithium-sulfur batteries. The invention firstly forms a colloid substance by complexing urea and metal salt in an ethanol solvent, and then grinds and mixes the colloid substance with functional additives such as sodium chloride and anhydrous potassium citrate, and then treats the colloid substance with a Joule heat device to prepare a carbon defect-rich Mn-loaded composite material. 3 O 4 The porous lithium-sulfur battery composite material has a rich multi-level pore structure and optimizes the Mn 3 O 4 The dispersion of Mn and the introduction of defects inside its crystals increase the number, intrinsic activity and conductivity of Mn catalytic sites, effectively accelerate the polysulfide conversion reaction in lithium-sulfur batteries, and show excellent electrocatalytic activity and stability for the conversion reaction of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material, belonging to the technical field of preparation of lithium-sulfur battery positive electrode materials. Background Art

[0002] Lithium-sulfur batteries (LSBs) stand out among the next generation of new energy storage devices due to their high energy density (2567kW / kg), high specific capacity (1672mAh / g), abundant sulfur resources and environmental friendliness. However, the commercial application of LSBs has encountered some challenging bottlenecks. For example, the insulation of the charge and discharge products (S8 and Li2S2 / Li2S), the drastic volume change during the cycle, the shuttling of intermediate species polysulfide ions and the slow kinetic conversion limit the further development of lithium-sulfur batteries. Therefore, the development of an efficient lithium-sulfur battery cathode material that can accelerate the conversion of polysulfide ions and inhibit the shuttling effect plays a vital role in improving battery performance.

[0003] A large number of studies have shown that transition metal oxides accelerate the conversion of polysulfides during the reaction of lithium-sulfur batteries, and at the same time confine polysulfides by forming chemical bonds between metal-sulfur, oxygen and lithium in lithium polysulfide, thereby inhibiting the "shuttle effect". Among them, manganese-based oxides have excellent environmental friendliness, abundant reserves, and strong polysulfide adsorption capacity, and are a very promising class of sulfur main materials for lithium-sulfur (Li-S) batteries. However, the conductivity of manganese-based oxides is usually not very ideal and the catalytic activity is limited, resulting in poor performance of lithium-sulfur batteries, so it is very necessary to develop a simple and efficient method for modifying manganese-based oxides. In the prior art, the main method is to use a composite with a carbon material with good conductivity, which can not only improve the conductivity of manganese-based oxides, but also improve its dispersibility, which is conducive to exposing more active sites and showing better electrochemical performance. However, the intrinsic catalytic activity of the unit point of manganese-based oxides has not been improved, resulting in limited improvement in the overall electrochemical performance of manganese-based oxides. In view of the above shortcomings, it is of great significance to develop a lithium-sulfur battery positive electrode material that can not only improve the conductivity and dispersibility of manganese-based oxides, but also enhance the intrinsic catalytic activity of manganese-based oxide unit points, thereby significantly improving the reaction kinetics.

[0004] The Chinese invention patent document with publication number CN117548105A discloses an α-MnO2 nanorod loaded RuO2 lithium-sulfur battery positive electrode catalyst and its preparation method. The method uses the synthesized α-MnO2 nanorod as a carrier, impregnates it in a RuCl3 aqueous solution, and finally calcines it in a tubular furnace to prepare the α-MnO2 nanorod loaded RuO2 lithium-sulfur battery positive electrode catalyst. The essence of this patent is to use RuO2 with good conductivity and strong adsorption capacity for polysulfides, thereby inhibiting polysulfide shuttle and reducing the energy barrier of solid-liquid conversion, thereby promoting the overall catalytic activity, but the Mn active center is not effectively regulated. In addition, Ru is a precious metal with scarce reserves and high cost, which is not conducive to industrial production.

[0005] The Chinese invention patent document with publication number CN110600690A discloses a zeolite imidazole framework-derived nitrogen-doped hierarchical porous carbon @ manganese tetraoxide @ carbon / sulfur (N-HPC@Mn3O4@NC / S) and its preparation method and application. The method first heat-treats the mesoporous carbon derived from the zeolite imidazole framework at 900-950°C to obtain N-HPC, then hydrothermally reacts N-HPC with potassium permanganate to obtain nitrogen-doped hierarchical porous carbon @ manganese tetraoxide derived from the zeolite imidazole framework; the nitrogen-doped hierarchical porous carbon @ manganese tetraoxide derived from the zeolite imidazole framework is dispersed in water, and then an alkaline solution and dopamine are added, and the nitrogen-doped hierarchical porous carbon @ manganese tetraoxide @ carbon / sulfur derived from the zeolite imidazole framework is obtained by stirring, filtering, drying, and high-temperature calcination. This method requires cumbersome wet chemical and heat treatment steps, which consumes a lot of time and energy. The essence of this patent is to improve the conductivity through the composite of carbon materials and Mn3O4, inhibit the "shuttle effect" of lithium polysulfide, and inhibit the volume expansion of sulfur during charging and discharging, thereby improving the performance of lithium-sulfur batteries. It does not involve the improvement of the conductivity of carbon materials and the optimization of the intrinsic catalytic activity of Mn3O4.

[0006] The Chinese invention patent document with publication number CN101901916A discloses a carbon-supported manganese tetraoxide composite catalytic material and a preparation method. Carbon black is added to a manganese nitrate solution for impregnation to obtain carbon black adsorbing manganese nitrate, and then dried, ground, and calcined at high temperature to obtain a carbon-supported manganese tetraoxide composite catalytic material. This preparation method also requires the carbon black to be pretreated with acid or alkali, and after pretreatment, it needs to be rinsed with a large amount of clean water. Not only is the preparation process cumbersome, but it also causes a waste of resources. In addition, the use of traditional calcination methods such as muffle furnaces can easily cause the collapse of the pore structure (smaller pore size) and the absence of defects (reduced defects), that is, the pore size range becomes smaller and the defect content is less, which leads to a decrease in the electrochemical performance of the material. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material, which can improve the preparation efficiency of the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material and reduce energy consumption, and can significantly improve the intrinsic catalytic activity of the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material, can effectively accelerate the polysulfide conversion reaction in the lithium-sulfur battery, and show excellent electrocatalytic activity and stability in the lithium-sulfur battery reaction.

[0008] To achieve this object, the technical solution of the present invention is:

[0009] A method for preparing a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material comprises the following steps:

[0010] (1) dissolving urea and manganese chloride tetrahydrate in ethanol to obtain a mixed solution;

[0011] (2) stirring the mixed solution at 50-80°C for 20-30 hours to obtain a colloid;

[0012] (3) The colloid, sodium chloride and anhydrous potassium citrate are mixed and ground into powder, and then the powder is placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment is performed in air or other oxygen-containing atmospheres. After washing and vacuum drying, a carbon defect-rich loaded Mn3O4-type porous lithium-sulfur battery composite material is obtained.

[0013] The inventors found in the experimental process of step (2) that when the reaction temperature is lower than 50°C, no colloid can be obtained after stirring the reaction for 30 hours; when the temperature exceeds 80°C, the mixed solution boils, causing the solution to splash, which is somewhat dangerous. Therefore, the reaction conditions must be properly controlled.

[0014] Furthermore, in step (1), the ratio of urea, manganese chloride tetrahydrate and ethanol in the mixed solution is 1 g: 1.5-2.5 g: 50-75 mL.

[0015] Furthermore, in step (3), the usage ratio of the colloid, sodium chloride and anhydrous potassium citrate is 1g:1-1.2g:0.5-0.7g.

[0016] Furthermore, in step (3), the conditions of Joule heat treatment are: heat treatment temperature 400-1000°C, heating rate 1000-2500°C / s, and Joule heat treatment times 2-10 times. Joule heat treatment is heating from room temperature to the target temperature, and then naturally cooling to room temperature, which is represented as one time.

[0017] Furthermore, in step (3), the washing conditions are: washing with deionized water and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80°C, drying time 18-24h.

[0018] Another object of the present invention is to provide an application of a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material prepared by the above method, which is applied to the positive electrode of a lithium-sulfur battery.

[0019] Specifically, the application includes the following steps:

[0020] (1) mixing a carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material with sublimated sulfur in a mass ratio of 1:3-10, placing the mixture into a sealed container, and heating the mixture at 140-180°C for 12-18h to solidify the sulfur, thereby obtaining a lithium-sulfur battery positive electrode material;

[0021] (2) Under inert atmosphere conditions, the lithium-sulfur battery positive electrode material, lithium foil negative electrode, polypropylene porous membrane separator and electrolyte are assembled into a button battery, and then the electrochemical performance test is carried out on the battery system.

[0022] The beneficial effects of the present invention are:

[0023] (1) Compared with the traditional calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high catalyst preparation efficiency, and low energy consumption. At the same time, it ensures that the catalyst has high activity and stability, which helps to inhibit the collapse of the pore structure (the pore size range becomes smaller) and the loss of defects (defects are reduced) at high temperatures.

[0024] (2) The present invention introduces sodium chloride and anhydrous potassium citrate as pyrolysis additives. The two have a synergistic effect, forming a molten salt with strong polarity and releasing a large amount of CO2 during the pyrolysis process, thereby generating a local extreme environment of high temperature and high pressure, and increasing the porosity of the pyrolysis product material; at the same time, during the high-temperature calcination process, chloride ions will corrode the material and cations will be modified and doped into the material, resulting in a large number of defects in the porous carbon material and Mn3O4 crystals, respectively, thereby increasing the conductivity of the material and improving the intrinsic activity of Mn3O4. However, after multiple washings with deionized water and ethanol, the excess chloride ions and potassium ions can be washed away and will not corrode the electrode material; in addition, during the calcination process, the rapid heating and cooling characteristics of the Joule heat treatment technology are used to greatly slow down the growth time of the Mn3O4 crystals, and the formation of carbon defects provides more nucleation sites for the growth of Mn3O4, which together promote the formation of small-sized Mn3O4 and significantly increase the number of catalytic active sites of Mn3O4.

[0025] (3) The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material prepared by the present invention not only has good conductivity, but also has more active sites and higher intrinsic activity. Its specific surface area and pore size range as well as carbon defect structure content (I D / I G ) are 552.56-589.78m respectively 2 / g, 4-60nm, 0.87-0.97, and outstanding performance in the positive electrode of lithium-sulfur batteries. At a high rate of 2C, the initial specific capacity of the lithium-sulfur battery is as high as 670.4-722.2mAh / g. After 500 cycles, the capacity retention rate is 82.3-87.6%, and the recovery rate from 2C to 0.1C is 91.5-95.0%. It shows excellent high-rate capacity, high stability, high rate, and reversibility in the lithium-sulfur battery reaction, and has broad industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a high-resolution transmission electron microscopy (HR-TEM) image of the carbon-defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material of Example 1;

[0027] Figure 2 This is a test diagram of the electrochemical long cycle performance of the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material of Example 1 at a 2C rate;

[0028] Figure 3 This is a high rate test diagram of the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material of Example 1 at 0.1-2C. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0030] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0031] In a specific embodiment of the present invention, the Joule heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0032] (1) Add 1 g urea and 2 g manganese chloride tetrahydrate into 60 mL ethanol and perform ultrasonic treatment until they are completely dissolved to obtain a mixed solution;

[0033] (2) stirring the mixed solution at 70°C for 24 hours to obtain a colloid;

[0034] (3) 1g of colloid, 1.1g of sodium chloride and 0.6g of anhydrous potassium citrate were mixed and ground into powder in a mortar, and then the powder was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 6 times in an air atmosphere, the Joule heat treatment temperature was 800°C, and the Joule heat treatment heating rate was 1500°C / s. After washing with deionized water and ethanol four times respectively, and vacuum drying at 70°C for 22h, a carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material was obtained. In addition, in this embodiment, the powder was subjected to Joule heat treatment in an air atmosphere. The inventors found that the Joule heat treatment in an oxygen-containing atmosphere in other embodiments can also achieve the purpose of the invention.

[0035] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to high-resolution transmission electron microscopy (HR-TEM) test, nitrogen full adsorption (N2-BET) test, and Raman spectroscopy test, respectively. Figure 1 , Table 1, wherein the N2-BET test includes specific surface area test and pore size distribution test, and the pore size distribution test result of N2-BET is the full pore size distribution based on NLDFT model.

[0036] Depend on Figure 1 It can be seen that the interplanar spacing is 0.25 nm, corresponding to the (222) crystal plane of the Mn3O4 crystal. In addition, a large number of lattices in the figure are distorted and some atoms are missing, indicating that there are a large number of defects in the Mn3O4 crystal. These defect sites can promote the adsorption of polysulfides in the catalytic reaction, thereby improving the performance of the positive electrode material of the lithium-sulfur battery.

[0037] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 552.56m 2 / g, 4-60nm, 0.97, among which I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, when I D / I GWhen >0.6 (ordinary conventional materials), it indicates good carbon defects.

[0038] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) is used for lithium-sulfur battery testing, including the following application steps:

[0039] ① The carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material and sublimated sulfur were mixed in a mass ratio of 1:5 and loaded into a reactor lined with polytetrafluoroethylene, and heated at 160°C for 16 hours to solidify sulfur to obtain a lithium-sulfur battery positive electrode material;

[0040] ②In an inert atmosphere glove box, lithium-sulfur battery cathode material, lithium foil anode, polypropylene porous membrane separator and electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) were assembled into button cells. The electrochemical long cycle performance of the battery was tested at 2C rate and high rate test at 0.1-2C on the CT-4008-5A6V system. The test results are shown in Figure 2 and Figure 3 .

[0041] Depend on Figure 2 It can be seen that the first-cycle discharge capacity at a 2C rate is 722.2 mAh / g. After 500 cycles, the capacity is maintained at 633.8 mAh / g. The capacity decay rate per cycle is 0.0245%. After 500 cycles, the capacity retention rate reaches 87.6%, which has good cycle stability and a high capacity decay rate.

[0042] Depend on Figure 3 It can be seen that at the high charge and discharge rate of 0.1-2C, the capacities reached 1220.2mAh / g, 1155.5mAh / g, 1080.5mAh / g, 950.8mAh / g and 722.2mAh / g at 0.1C, 0.2C, 0.5C, 1C and 2C respectively. When switched to 0.1C, the capacity reached 1159.2mAh / g, and the recovery rate reached 95%, indicating that it has highly reversible electrochemical properties and exhibits good rate performance. Example 2

[0043] (1) Add 1 g of urea and 1.5 g of manganese chloride tetrahydrate into 50 mL of ethanol and perform ultrasonic treatment until they are completely dissolved to obtain a mixed solution;

[0044] (2) stirring the mixed solution at 50°C for 30 hours to obtain a colloid;

[0045] (3) 1 g of colloid, 1 g of sodium chloride and 0.5 g of anhydrous potassium citrate were mixed and ground into powder using a mortar. The powder was then placed in the groove of a graphite sample stage of a Joule heating device and subjected to Joule heat treatment 10 times in an air atmosphere at a Joule heat treatment temperature of 400 °C and a Joule heat treatment heating rate of 1000 °C / s. The powder was washed three times with deionized water and ethanol respectively and vacuum dried at 50 °C for 24 h to obtain a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material.

[0046] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0047] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 589.78m 2 / g, 4-50nm, 0.87, the material belongs to the multi-level pore structure material of mesopore and macropore, among which I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, when I D / I G When >0.6, it indicates good carbon defects.

[0048] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) is used for lithium-sulfur battery testing, including the following application steps:

[0049] ① The carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material and sublimated sulfur were mixed in a mass ratio of 1:3 and loaded into a reactor lined with polytetrafluoroethylene, and heated at 140°C for 18 hours to solidify sulfur to obtain a lithium-sulfur battery positive electrode material;

[0050] ② In an inert atmosphere glove box, the lithium-sulfur battery positive electrode material, lithium foil negative electrode, polypropylene porous membrane separator and electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) were assembled into a button battery. The battery was subjected to electrochemical long cycle performance test at 2C rate and high rate test at 0.1-2C on the CT-4008-5A6V system. The test results are shown in Table 1.

[0051] As shown in Table 1, the first cycle discharge capacity at 2C rate is 670.4 mAh / g, and the capacity retention rate reaches 82.3% after 500 cycles, which has good cycle stability and high capacity attenuation rate.

[0052] At a high charge and discharge rate of 0.1-2C, when switching from 2C to 0.1C, the capacity recovery rate reached 91.5%, indicating highly reversible electrochemical properties and showing good rate performance. Example 3

[0053] (1) Add 1 g urea and 2.5 g manganese chloride tetrahydrate into 75 mL ethanol and perform ultrasonic treatment until they are completely dissolved to obtain a mixed solution;

[0054] (2) stirring the mixed solution at 80°C for 20 hours to obtain a colloid;

[0055] (3) 1 g of colloid, 1.2 g of sodium chloride and 0.7 g of anhydrous potassium citrate were mixed and ground into powder in a mortar. The powder was then placed in the groove of the graphite sample stage of a Joule heating device and subjected to Joule heat treatment twice in an air atmosphere at a Joule heat treatment temperature of 1000°C and a Joule heat treatment heating rate of 2500°C / s. The powder was washed with deionized water and ethanol five times respectively and vacuum dried at 80°C for 18 h to obtain a carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material.

[0056] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0057] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 573.52m 2 / g, 4-55nm, 0.91, the material belongs to the multi-level pore structure material of mesopore and macropore, among which I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, when I D / I G When >0.6, it indicates good carbon defects.

[0058] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) is used for lithium-sulfur battery testing, including the following application steps:

[0059] ① The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material and sublimated sulfur were mixed in a mass ratio of 1:10 and loaded into a reactor lined with polytetrafluoroethylene, and heated at 180°C for 12 hours to solidify sulfur to obtain a lithium-sulfur battery positive electrode material;

[0060] ② In an inert atmosphere glove box, the lithium-sulfur battery positive electrode material, lithium foil negative electrode, polypropylene porous membrane separator and electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) were assembled into a button cell. The battery was subjected to electrochemical long cycle performance test at 2C rate and high rate test at 0.1-2C on the CT-4008-5A6V system. The test results are shown in Table 1.

[0061] As shown in Table 1, the first cycle discharge capacity at 2C rate is 697.7 mAh / g, and the capacity retention rate reaches 83.4% after 500 cycles, which has good cycle stability and high capacity attenuation rate.

[0062] At a high charge and discharge rate of 0.1-2C, when switching from 2C to 0.1C, the capacity recovery rate reached 94.5%, indicating highly reversible electrochemical properties and showing good rate performance. Example 4

[0063] (1) Add 1 g of urea and 1.8 g of manganese chloride tetrahydrate to 55 mL of ethanol and perform ultrasonic treatment until they are completely dissolved to obtain a mixed solution;

[0064] (2) stirring the mixed solution at 65°C for 26 hours to obtain a colloid;

[0065] (3) 1 g of colloid, 1.2 g of sodium chloride and 0.6 g of anhydrous potassium citrate were mixed and ground into powder using a mortar. The powder was then placed in the groove of a graphite sample stage of a Joule heating device and subjected to Joule heat treatment six times in an air atmosphere at a Joule heat treatment temperature of 800 °C and a Joule heat treatment heating rate of 1500 °C / s. The powder was then washed four times with deionized water and ethanol respectively and vacuum dried at 70 °C for 22 h to obtain a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material.

[0066] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0067] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 562.32m 2 / g, 4-59nm, 0.96, among which I D / I G The ratio is the D band (1353 cm -1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, when I D / I G When >0.6, it indicates good carbon defects.

[0068] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0069] As shown in Table 1, the first cycle discharge capacity at 2C rate is 716.3 mAh / g, and the capacity retention rate reaches 85.6% after 500 cycles, which has good cycle stability and high capacity attenuation rate.

[0070] At a high charge and discharge rate of 0.1-2C, when switching from 2C to 0.1C, the capacity recovery rate reached 95.0%, indicating highly reversible electrochemical properties and showing good rate performance. Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 1 is that the heating device in step (3) is different, the Joule heating device is replaced with a muffle furnace, and the other steps remain unchanged. The specific operation is as follows:

[0072] 1g of colloid, 1.1g of sodium chloride and 0.6g of anhydrous potassium citrate were mixed and ground into powder with a mortar. The powder was then placed in a muffle furnace and calcined in an air atmosphere at a calcination temperature of 1800°C and a heating rate of 5°C / min. The reaction was kept warm for 2h, washed five times with deionized water and ethanol respectively, and vacuum dried at 80°C for 18h to obtain a carbon defect-rich loaded Mn3O4-type porous lithium-sulfur battery composite material.

[0073] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0074] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 452.25m 2 / g, 3-50nm, 0.68, the material belongs to the multi-level pore structure material of mesopore and macropore, but the I of comparative example 1 D / I G The value is much smaller than that of Example 1. D / I G value (0.96).

[0075] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0076] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 2C is 526.2 mAh / g, and the capacity retention rate reaches 78.5% after 500 cycles; at a high charge and discharge rate of 0.1-2C, when switching from 2C to 0.1C, the capacity recovery rate reaches 75.2%, and its capacity, cycle retention and recovery rate are much lower than those in Example 1, indicating that the traditional calcination method causes the specific surface area, pore size range, and carbon defect content of the material to be much lower than the calcination method using a Joule heat device, which in turn leads to poor catalytic performance. Comparative Example 2

[0077] The difference between Comparative Example 2 and Example 1 is that the additives sodium chloride and anhydrous potassium citrate are not used in step (3), and the other parts remain unchanged.

[0078] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0079] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 248.26m 2 / g, 3-30nm, 0.62, the material belongs to the multi-level pore structure material of mesopore and macropore, but the I of comparative example 2 D / I G The value is much smaller than that of Example 1. D / I G value (0.96). This is mainly because sodium chloride and anhydrous potassium citrate will form highly polar molten salts during high-temperature calcination and release a large amount of CO2 during pyrolysis, thereby producing a local extreme environment of high temperature and high pressure, increasing the porosity of the pyrolysis product material; at the same time, chloride ion corrosion and cation modification can induce pyrolysis products, resulting in a large number of defects in porous carbon materials and Mn3O4 crystals, respectively, thereby increasing the conductivity of the material and improving the intrinsic activity of Mn3O4.

[0080] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0081] As can be seen from Table 1, the first cycle discharge capacity at a rate of 2C is 432.8 mAh / g, and the capacity retention rate reaches 69.4% after 500 cycles; at a high charge and discharge rate of 0.1-2C, when switching from 2C to 0.1C, the capacity recovery rate reaches 74.2%, and its capacity and cycle retention and recovery rate are much lower than those in Example 1, indicating that the additives sodium chloride and anhydrous potassium citrate will affect the specific surface area, pore size range, and carbon defect content of the material, thereby leading to poor catalytic performance. Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 1 is that the additive sodium chloride is not used in step (3), and the other steps remain unchanged.

[0083] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0084] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 520.52m 2 / g, 4-53nm, 0.84, the material belongs to the multi-level pore structure material of mesopore and macropore, but the I of comparative example 3 D / I G The value is much smaller than that of Example 1. D / I G This is mainly because the thermal decomposition efficiency of anhydrous potassium citrate alone is limited, resulting in a smaller pore size; at the same time, the induced material of anhydrous potassium citrate has fewer defects.

[0085] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0086] As shown in Table 1, the first cycle discharge capacity at 2C rate is 640.8 mAh / g, and the capacity retention rate reaches 80.6% after 500 cycles; at 0.1-2C charge and discharge high rate, when switching from 2C to 0.1C, the capacity recovery rate reaches 85.2%, and its capacity and cycle retention and recovery rate are much lower than those in Example 1, indicating that the additive sodium chloride affects the specific surface area, pore size range, and carbon defect content of the material, thereby resulting in poor catalytic performance. Therefore, sodium chloride and anhydrous potassium citrate have a synergistic effect. Comparative Example 4

[0087] The difference between Comparative Example 4 and Example 1 is that the additive anhydrous potassium citrate is not used in step (3), and the other parts remain unchanged.

[0088] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0089] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 500.52m 2 / g, 4-40nm, 0.78, the material belongs to the multi-level pore structure material of mesopore and macropore, but the I of comparative example 4 D / I G The value is much smaller than that of Example 1. D / I G This is mainly because the pyrolysis efficiency of sodium chloride alone is limited, resulting in a smaller pore size; at the same time, the chloride ion corrosion of sodium chloride alone is limited, resulting in fewer defects in the material.

[0090] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0091] As shown in Table 1, the first cycle discharge capacity at 2C rate is 580.8mAh / g, and the capacity retention rate reaches 78.6% after 500 cycles; at 0.1-2C charge and discharge high rate, when switching from 2C to 0.1C, the capacity recovery rate reaches 82.2%, and its capacity and cycle retention and recovery rate are much lower than those in Example 1, indicating that the additive anhydrous potassium citrate will affect the specific surface area, pore size range, and carbon defect content of the material, thereby resulting in poor catalytic performance. It can be seen from Comparative Example 3 that sodium chloride and anhydrous potassium citrate have a synergistic effect. Comparative Example 5

[0092] The difference between Comparative Example 5 and Example 1 is that ethanol is not used as the solvent in step (1), but ethanol is replaced by water, and the other conditions remain unchanged.

[0093] During the experiment, it was found that when ethanol was replaced with water, a colloid was not formed and solid particles were obtained, that is, ethanol was the key factor in the formation of a colloid.

[0094] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was subjected to N2-BET test and Raman spectrum test. The test results are shown in Table 1. The test method is the same as that in Example 1.

[0095] As shown in Table 1, the specific surface area, pore size range, and carbon defect structure content (I D / I G ) are 450.23m 2 / g, 4-50nm, 0.72, the material belongs to the multi-level pore structure material of mesopore and macropore, but the I of comparative example 5 D / I G The value is much smaller than that of Example 1. D / I G value (0.96).

[0096] The carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material obtained in step (3) was used for lithium-sulfur battery testing. The testing method was the same as that in Example 1. The test results are shown in Table 1.

[0097] As shown in Table 1, the first cycle discharge capacity at 2C rate is 507.8mAh / g, and the capacity retention rate reaches 74.6% after 500 cycles; at 0.1-2C charge and discharge high rate, when switching from 2C to 0.1C, the capacity recovery rate reaches 78.9%, and its capacity and cycle retention and recovery rate are much lower than those in Example 1, indicating that the colloid state will affect the specific surface area, pore size range, and carbon defect content of the material, thereby leading to poor electrochemical performance. Therefore, ethanol is of great significance as a solvent, because the substance in the colloid state will lock a part of the solvent molecules, and the sample will be more fluffy during the calcination process. When combined with the Joule heat treatment technology, it has a synergistic effect, so that the carbon defect-rich loaded Mn3O4-type porous lithium-sulfur battery composite material has a higher specific surface area and carbon content.

[0098]

[0099] As can be seen from the above, the materials prepared in Examples 1-4 have larger specific surface areas and I D / I G Value(I D / I GThe larger the value, the more carbon defects there are). This is mainly because sodium chloride and anhydrous potassium citrate are functional additives. At high temperatures, sodium chloride will form a molten salt with a strong polarity with anhydrous potassium citrate and decompose to produce a large amount of CO2, which can be used as a pore-forming agent to increase the specific surface area of ​​the carbon material. Under the extreme conditions of high temperature and high pressure caused by the release of CO2, the molten salt can further corrode the carbon material and interfere with the growth of the Mn3O4 crystal and form a large number of carbon defects and introduce a large number of defects in the Mn3O4 crystal. The rapid cooling characteristics of the Joule heat device can effectively retain these defects formed at high temperatures. Therefore, the large specific surface area, rich defects and multi-level pore structure make the carbon-defect-rich Mn3O4-type porous lithium-sulfur battery composite material show excellent performance, far exceeding the performance of materials prepared by traditional calcination methods and without adding functional additives. In addition, ethanol as a reaction solvent is a key factor in the preparation method. The substance in a colloidal state will lock a part of the solvent molecules, making the sample more fluffy during the calcination process. When combined with Joule heat treatment technology, it has a synergistic effect, making the carbon-defect-rich loaded Mn3O4-type porous lithium-sulfur battery composite material have a higher specific surface area and carbon content.

[0100] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material, characterized in that: The following steps are involved: (1) dissolving urea and manganese chloride tetrahydrate in ethanol to obtain a mixed solution; (2) stirring the mixed solution at 50-80°C for 20-30 hours to obtain a colloid; (3) The colloid, sodium chloride and anhydrous potassium citrate are mixed and ground into powder, and then the powder is placed in the groove of the graphite sample stage of the Joule heating device, and then subjected to Joule heat treatment in an air atmosphere. After washing and vacuum drying, a carbon defect-rich loaded Mn3O4-type porous lithium-sulfur battery composite material is obtained.

2. The method for preparing the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (1), the ratio of urea, manganese chloride tetrahydrate and ethanol in the mixed solution is 1 g: 1.5-2.5 g: 50-75 mL.

3. The method for preparing the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (3), the proportion of the colloid, sodium chloride and anhydrous potassium citrate is 1g:1-1.2g:0.5-0.7g.

4. The method for preparing the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (3), the conditions of the Joule heat treatment are: a heat treatment temperature of 400-1000°C, a heating rate of 1000-2500°C / s and a Joule heat treatment number of 2-10 times.

5. The method for preparing the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material according to claim 1, characterized in that: Furthermore, in step (3), the washing conditions are: washing with deionized water and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C. and drying time 18-24 h.

6. An application of a carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.

7. The use of the carbon defect-rich Mn3O4-loaded porous lithium-sulfur battery composite material according to claim 6, characterized in that: The steps include: (1) mixing a carbon defect-rich Mn3O4-type porous lithium-sulfur battery composite material with sublimated sulfur in a mass ratio of 1:3-10, placing the mixture into a sealed container, and heating the mixture at 140-180°C for 12-18h to solidify the sulfur, thereby obtaining a lithium-sulfur battery positive electrode material; (2) Under inert atmosphere conditions, the lithium-sulfur battery positive electrode material, lithium foil negative electrode, polypropylene porous membrane separator and electrolyte are assembled into a button battery, and then the electrochemical performance test is carried out on the battery system.

Citation Information

Patent Citations

  • Carbon-carried manganese tetraoxide composite catalytic material and preparation method thereof

    CN101901916A

  • Alpha-MnO2 nanorod loaded RuO2 lithium-sulfur battery positive electrode catalyst and preparation method thereof

    CN117548105A

  • Preparation method for cathode material of lithium-sulfur battery

    CN109309217A

  • Zeolite-imidazole-framework derived nitrogen-doped hierarchical porous carbon@trimanganese tetroxide@carbon / sulfur and preparation method and application thereof

    CN110600690A